Moist‐Electric Generator with Efficient Output and Scalable Integration Based on Carbonized Polymer Dot and Liquid Metal Active Electrode. (20th February 2023) - Li, Qijun; Qin, Yukun; Cheng, Dengke; Cheng, Ming; Zhao, Hongjia; Li, Lvzhou; Qu, Songnan; Tan, Jing; Ding, Jianning
Abstract: Moisture‐enabled electricity generation (MEG) is highly promising in next‐generation energy conversion. However, the practical applications of existing MEG devices are limited due to their low current and voltage outputs, strong dependence on high moisture, and inflexible nature. Herein, an efficient MEG integrated with flexible, all‐weather, and scalable fabrication characteristics based on the rational combination of carbonized polymer dots (CPDs) and liquid metal (LM) active electrodes is developed for the first time. Remarkably, the fabricated MEG device can produce a stable voltage output of 800 mV and a record high current density of 1640 µA cm −2 . Even at a low air humidity of 15%, the MEG device can provide a high voltage output of 0.65 V and a considerable current density of 12 µA cm −2 . The prompted diffusion of hydrogen ions in CPDs and the additional metal ions ionized from the LM electrode contribute synergistically to the high electricity generation. Additionally, the device can be easily integrated on various flexible substrates and generate an ultrahigh voltage of 210 V to power commercial electronics, showing great potential in large‐scale fabrication and application. Abstract : A high‐performance moisture‐enabled electricity generation (MEG) device with an easy scale‐up, all‐weather and flexible characteristics is fabricated based on the rational combination of carbonized polymer dots and liquid metal active electrode for the first time. The MEG device can produce a stable voltage output of 0.8 V and a record high current density of 1.64 mA cm −2 .